Strong cation exchange-based fractionation of Lys-N-generated peptides facilitates the targeted analysis of post-translational modifications. - Taouatas, N; Altelaar, A; Drugan, M; Helbig, A; Mohammed, S; Heck, A (2009)
In proteomics multi-dimensional fractionation techniques are widely used to reduce the complexity of peptide mixtures subjected to mass spectrometric analysis. Here, we describe the sequential use of strong cation exchange and reversed phase liquid chromatography in the separation of peptides generated by a relatively little explored metallo-endopeptidase with Lys-N cleavage specificity. When such proteolytic peptides are subjected to low-pH strong cation exchange we obtain fractionation profiles in which peptides from different functional categories are well separated. The four categories we distinguish and are able to separate to near completion are (I) acetylated N-terminal peptides; (II) singly phosphorylated peptides containing a single basic (Lys) residue; (III) peptides containing a single basic (Lys) residue; and (IV) peptides containing more than one basic residue. Analyzing these peptides by LC-MS/MS using an ion trap with both collision as well as electron transfer-induced dissociation provides unique optimal targeted strategies for proteome analysis. The acetylated peptides in category I can be identified confidently by both CID and ETcaD, whereby the ETcaD spectra are dominated by sequence informative Z-ion series. For the phosphorylated peptides in category II and the "normal" single Lys containing peptides in category III ETcaD provides unique straightforward sequence ladders of c'-ions, from which the exact location of possible phosphorylation sites can be easily determined. The later fractions, category IV, require analysis by both ETcaD and CID, where it is shown that electron transfer dissociation performs relatively well for these multiple basic residues containing peptides, as is expected. We argue that the well resolved separation of functional categories of peptides observed is characteristic for Lys-N-generated peptides. Overall, the combination of Lys-N proteolysis, low-pH strong cation exchange, and reversed phase separation, with CID and ETD induced fragmentation, adds a new very powerful method to the toolbox of proteomic analyses.